Unilateral persistent hyperplastic tunica vasculosa lentis and persistent hyperplastic primary vitreous in a rabbit. (27th January 2015) - Boillot, Thomas; Graille, Mélanie; Williams, David; Rosolen, Serge G.
Abstract A 3‐month wild rabbit was presented for examination of ocular opacities in the left eye. A complete bilateral ocular examination including slit‐lamp examination, indirect ophthalmoscopy, tonometry, and ultrasound biomicroscopy was performed. Biomicroscopy of the lens of the left eye showed a retrolental fibrovascular membrane causing leukocoria. The opacity prevented biomicroscopy of the vitreous and funduscopy OS. No other disorder was present in either eye. Ultrasound examination did not show any difference between the right and left eye. Histopathological examination showed a 50‐μm thick, preretinal, retrolental, nonpigmented, fibrovascular tissue. Posterior synechiae were present, but no other lesion of the posterior segment was found in this eye. These ocular abnormalities are consistent with a persistent hyperplastic tunica vasculosa lentis and persistent hyperplastic primary vitreous (PHTVL/PHPV), similar to those described in other species.